HIGH COGNITIVE ACTIVATION BY COMPLEX TASKS AS A TOOL OF DECREASING REPETITIONS AT TERTIARY LEVEL IN THE DEMOCRATIC REPUBLIC OF CONGO “Case of South Kivu Province’’ - Ghislain KUMBUKA KALIHOFU; Pierre MURHULA KAHETO; Samuel CIMANUKA KARONGO (IJRDO- Journal of Educational Research, 2020)
Pedagogical and psychological Research show that the teacher plays a determining role in helping students learn more during his or her studying process (Dembelé & Gauthier, 2004). The way the teaching sessions are handled methodological and presented by the teacher is one of the effective success of the learner considering both the student and the teacher as the best tool of cognitive activation .School authorities and educators around the country should then promote the teacher’s personal development with frequent in -service trainings around because these are essential for quality education; so ensuring that teachers and educators are empowered and well-trained should get prominence for schools (World Education Forum, 2015).During our study, the question of quality teaching and learning will be raised and the cognitive activation by complex tasks will be focused on as one of the approaches which may increase repetitions by students. In so doing, a scientific inquisitiveness has led our analysis and a number of questions came up to the mind such as: Why do students around my city have to repeat classes although enrolled as permanent ones and attending the class sessions regularly? Can repeating a class give more chance to the learner to improve or no? Can high cognitive activation by complex tasks enhance the system quality by decreasing repetitions? Can cognitive activation by tasks reduce the repetitions at tertiary level? Do repetitions have advantages and disadvantages at tertiary level, if so, what are they? What are the consequences of repetitions at tertiary level in the DRC education system? Regarding the questions mentioned above, we find worth to mention the context of the tertiary education in the DRCalso give the problem statement related to higher education in the DR Congo.